SMART2L: Smart Water Level and Leakage Detection - Hafiz Kadar, Haikal; Syarmila Sameon, Sera; Ezanee Rusli, Mohd. (International Journal of Engineering and Technology, 2018)
The Internet of Things (IoT) technology can assist in the effective conservation of resources and energy management. With IoT, managing water level and detecting leakage within water pipeline distribution system can be automated. This is the golden opportunity as the field of water management and distribution progress with the advancement of IoT. Water shortage has been part of the crucial complications that encountered by many municipalities around the globe and surplus during transmission has been acknowledged as the main problem. Thus, the key idea for this project is to design a real-time low cost wireless system called as SMART2L to prevent Non-Revenue Water (NRW) commonly known as unbilled water wastage. SMART2L integrates with Internet of Things (IoT) that will make a change to the way of people live and manage their water resources smartly.Â Â